Building the bacterial cell wall at the pole. (December 2016) - Howell, Matthew; Brown, Pamela JB
Graphical abstract: Highlights: Polymer-forming landmark proteins direct PG biosynthesis to specific locations. Bacterial scaffolds to provide mechanical support at growth poles. Polar growing bacteria exhibit tip splitting behavior. Polar cell elongation must be coordinated with cell cycle progression. Abstract : Polar growth is the predominant mode of cell wall extension in the Actinobacteria and the alphaproteobacterial clade Rhizobiales. The observation of polar elongation in taxonomically diverse bacteria suggests that polar growth may have evolved independently. Indeed, the regulatory mechanisms governing the assembly of cell wall biosynthesis machinery at the pole are distinct in the Actinobacteria and Rhizobiales. Here we highlight recent advances in our understanding of polar growth mechanisms in bacteria, with an emphasis on Streptomyces and Agrobacterium. This review illustrates that common themes are emerging in the regulation of polar growth in diverse bacteria. Emerging themes include the use of landmark proteins to direct growth to the pole and coordination of polar growth with cell-cycle progression.